Self-organization of nickel nanoparticles dispersed in acetone: from separate nanoparticles to three-dimensional superstructures - Hernández-Pérez, I. (2016)
Sonochemical synthesis of monodisperse nickel nanoparticles (Ni-NPs) by reduction of Ni acetylacetonate in the presence of polyvinylpyrrolidone stabilizer is reported. The Ni-NPs size is readily controlled to 5 nanometer diameter with a standard deviation of less than 5%. The as-prepared Ni-NPs sample was dispersed in acetone, for 4 weeks. For structural analysis was not applied to a magnetic field or heat treatment as key methods to direct the assembly. The transition from separate Ni-NPs into self-organization of three dimensions (3D) superstructures was studied by electron microscopy. Experimental analysis suggests that the translation and rotation movement of the Ni-NPs are governed by magnetic frustration which promotes the formation of different geometric arrangements in two dimensions (2D). The formation of 3D superstructures is confirmed from scanning electron microscopy revealing a layered domain that consists of staking of several monolayers having multiple well-defined supercrystalline domains, enabling their use for optical, electronic and sensor applications.